Oral Desensitization in Nursling with Cow's Milk Allergy - Carlos Alberto Sánchez Salguero (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2015)
Food allergy is a major public health problem affecting nearly 10 % of children in most industrialized countries. Unfortunately, there are no effective therapies for food allergy, relegating patients to simply avoid the offending foods and treating the reactions which occur on accidental exposure. Recently however, studies suggest that food immunotherapy may provide a promising new approach to food allergy, particularly using the oral form of immunotherapy (OIT). Enthusiasm for this approach though must be tempered because of the significant allergic reactions that often occur with OIT that tends to limit its use to patients with less severe disease. Actually this technique of desensitization is applied in child with ages over 5 years old, because many investigators think that this is the frontier from which the allergy is persistent all the life, and before this age the possibilities of natural tolerance to milk is very much probability. In contrast to this, are few investigational groups dedicated to try to desensitize children under 1 years old, and less in the first 6 months of the life, due to the high possibilities of secondary reactions, especially anaphylaxis.